Accurate detection of triple vessel disease in patients with exercise induced ST segment depression after infarction. Issue 2 (February 1987) - Mannering, D; Bennett, E D; Ward, D E; Dawkins, K; Dancy, M; Valantine, H; Mehta, N
Abstract : The severity of coronary artery disease is an important determinant of prognosis after acute myocardial infarction. The ability of a symptom limited exercise test to predict the presence of triple vessel disease was assessed in 221 patients three weeks after infarction. Coronary angiography was performed in patients with exercise induced ST segment depression. The presence of ST segment depression alone was poorly indicative of triple vessel disease; however, some specific features of ST segment changes on exercise were of predictive value. Downsloping ST segment configuration alone or horizontal ST segment depression associated with an early onset and a late recovery time after exercise correctly identified 30 (90%) of 33 patients with triple vessel disease whereas it incorrectly identified only 6 (15%) of 39 patients with single and double vessel disease. An abnormal blood pressure response was also predictive. In patients with ST segment depression after infarction triple vessel disease can be detected accurately by a combination of the electrocardiographic and haemodynamic variables attained on exercise.